Social Movements and Leftist Governments in Latin America : Confrontation or Co-optation?. - Prevost, Gary (Zed Books, 2012)
"The simultaneous development of prominent social movements and the election of left and center-left governments has radically altered the political landscape in Latin America. Social Movements and Leftist Governments in Latin America moves beyond simple discussion of these social movements, shedding new light on how these social movements continue to operate in Latin America."--Provided by publisher.